Choline alphoscerate: insights between acquired certainties and future perspectives - Biggio, Giovanni; Mencacci, Claudio (Frontiers in Aging Neuroscience, 2025)
While mild cognitive impairment (MCI) is a risk factor for dementia, it is currently impossible to predict which patients will go on to develop dementia or Alzheimer’s disease. Given the projected global increase in dementia due to an increasingly aging population, there is an urgent need to develop pharmacological therapies to reduce symptoms of MCI, and to help delay its possible progression to dementia. Choline alphoscerate is a cholinergic precursor naturally found in the brain that has been identified as an essential nutrient and is available as a prescription drug. While the efficacy of choline alphoscerate on cognitive function is well established in patients with MCI, Alzheimer’s disease, and cognitive impairment of vascular origin, emerging evidence suggests that it has neuroprotective effects against β-amyloid injury and may be useful as a preventive therapy against development of Alzheimer’s disease in patients with MCI. Recent data also show that choline alphoscerate may be effective against non-cognitive symptoms of MCI (e.g., depression, anxiety, irritability, aggression, and apathy). Here we review pharmacological and clinical evidence regarding choline alphoscerate in order to highlight its usefulness in patients with MCI. The potential role of choline alphoscerate in promoting healthy sleep architecture is also explored.